Person-Environment Fit and Employee Creativity: The Moderating Role of Multicultural Experience - Wang, Kaiqing; Wang, Yijie (Frontiers in Psychology, 2018)
Previous research have demonstrated the positive effects of congruent personal and environmental characteristics on creativity. None of them, however, has tested the formal theory of person-environment fit for predicting creativity in the context of multicultural experiences. This study examined the effects of two versions of person-environment fit (Demands-abilities fit and Needs-supplies fit) on employee creativity in China, taking into account the moderating role of multicultural experiences. The results, based on the data of East Asian Social Survey in the Chinese General Social Survey (CGSS) in 2015, showed employees with demands-abilities fit have lower creativity than those with demands-abilities misfit; nevertheless, the demands-abilities fit creates a growing impact on employee creativity with increasing multicultural experience. Additionally, the higher the needs-supplies fit, the stronger the employee creativity; and, the needs-supplies fit creates a growing impact on employee creativity with increasing multicultural experience. It shows that different versions of person–environment fit have different effects on employee creativity and multicultural experience moderated the effects of person-environment fit on employee creativity. Implications for research and practice are discussed.